Distribution and Abundance of Deep Sea Fishes Along the West Coast of India - B., Madhusoodana Kurup; S., Venu (Fishery Technology, 2025)
Bathymetric and spatial distribution and abundance of the deep-sea finfish resources in the EEZ off west coast of India (200-750m) are discussed based on the results of three fishing cruises carried out from FORV Sagar Sampada during 1998-2000. Results indicate the existence of potentially rich unexploited deep sea finfish resources. The area between 7° and 9° N lat was found to be more productive with catch rates ranging from 660.5 -1185.6 kg.h1. Comparatively low catch rates were obtained between 10° and 11° N lat and 14° and 21° N lat with catch rates ranging from 18.0 to 41.3 kg.h1. Areas within 9o-10o N and 11°- 14° N lat contributed moderate catches with CPUE ranging from 75.79 to 229.17 kg.h1. Most productive depth ranges were found to be 201-300 and 301-400 m. Major species constituting the catches were Chlorophthalmus punctatus, Chlorophthalmus bicornis, Psenopsis cyanea, Neopinnula orientalis, Hoplostethus mediterraneus, Psenes squamiceps, Nettastoma parviceps and Priacanthus hamrur.